Partnering Early to Provide for Infants At Risk of Cerebral Palsy (PĒPI ARC): protocol for a feasibility study of a regional hub for early detection of cerebral palsy in Aotearoa New Zealand - Allermo Fletcher, Angelica; Kilgour, Gaela; Sandle, Meghan; Kidd, Sally; Sheppard, Alison; Swallow, Stephanie; Stott, Ngaire Susan; Battin, Malcolm; Korent, Wyllis; Williams, Sian A. (Frontiers in Pediatrics, 2024)
Introduction Cerebral palsy (CP) can now be diagnosed in infants with identified CP risk factors as early as three months of age; however, many barriers prevent equitable access to early detection pathways. The “Partnering Early to Provide for Infants At Risk of Cerebral Palsy” feasibility study (PĒPI ARC) seeks to trial a new approach to decrease inequitable health service in Aotearoa New Zealand for high-risk infants and their families. PĒPI ARC incorporates face-to-face clinics, an in-person and virtual Hub, and the use of telehealth to enable flexible access to CP assessments and support for health professionals in early CP detection. Methods and analysis A non-randomised feasibility study was conducted from a tertiary Neonatal Intensive Care Unit (NICU) in Wellington and included seven regional referral centres, servicing nearly 30% of the total population in New Zealand (NZ). The families of infants with a high risk of neurodevelopmental impairment and health professionals interacting with the Hub were invited to participate. Mixed methods were used to evaluate the (i) equitable implementation of an early detection pathway, (ii) acceptability, (iii) demand among families and health professionals, (iv) efficacy in relation to reducing the age of receipt of CP diagnosis, and (v) the experiences around communication and information sharing. Ethics and dissemination The NZ Health and Disability Ethics Committee approved this study (HDEC: 2022 FULL 13434). The findings will be disseminated in peer-reviewed journals, in conference presentations, and via professional networks. Clinical trial registration Australian New Zealand Clinical Trials Registry: ACTRN12623000600640.